Strategi Public Relations Kantor Wilayah Kemenkumham Sumatera Utara Membangun Citra Positif dan Kepercayaan Publik - Harahap, Andre Genesa; Humaizi; Zulkarnain, Iskandar (Unitri Press, 2025)
This study aims to determine how the public relations strategy of the North Sumatra Ministry of Law and Human Rights Regional Office is implemented in building a positive image and public trust, the obstacles faced in implementing the public relations strategy and the relationship model created between public relations and the public. This study uses a constructivism paradigm with a qualitative descriptive approach. Data collection techniques are carried out through in-depth interviews, participatory observation and document collection/literature studies. The important findings of this study are that the public relations of the North Sumatra Ministry of Law and Human Rights Regional Office has implemented a public relations strategy, namely managing relations, developing strategies and developing networks as an effort to build a positive image and public trust. However, the public relations strategy implemented by the Public Relations of the North Sumatra Ministry of Law and Human Rights Regional Office is still less effective in improving a positive image and public trust. Some of the problems faced are budget limitations, low human resources, the function of the Public Relations section as a one-stop information center that is not yet optimal, the competence of Public Relations in providing Public Relations materials is not good, and the lack of coordination and synergy between the Public Relations Section and other work units in terms of providing accurate and valid information. Abstrak Penelitian ini bertujuan untuk menganalisis bagaimana strategi public relations Kantor Wilayah Kementerian Hukum dan HAM Sumatera Utara yang diterapkan dalam membangun citra positif dan kepercayaan publik, hambatan-hambatan yang dihadapi dalam menjalankan strategi public relations tersebut maupun model hubungan yang tercipta antara public relations dengan public menggunakan teori Sugiyono. Penelitian ini menggunakan paradigma kontruktivisme dengan pendekatan deskriptif kualitatif. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi partisipatif dan pengumpulan dokumen/studi kepustakaan. Temuan penting penelitian ini adalah bahwa public relations Kantor Wilayah Kementerian Hukum dan HAM Sumatera Utara telah melakukan strategi public relations yakni mengelola relasi, mengembangkan strategi dan mengembangkan jaringan sebagai Upaya untuk membangun citra positif dan kepercayaan publik. Namun strategi public relations yang diimplementasikan oleh Humas Kantor Wilayah Kementerian Hukum dan HAM Sumatera Utara masih kurang efektif dalam meningkatkan citra positif dan kepercayaan publik. Beberapa permasalahan yang dihadapi adalah keterbatasan anggaran, sumber daya manusia masih rendah, fungsi bagian Humas sebagai pusat informasi satu pintu yang belum optimal, kompetensi Humas dalam menyediakan materi Humas belum baik, serta kurangnya koordinasi dan sinergitas antara Bagian Humas dengan unit kerja lainnya dalam hal menyediakan informasi yang akurat dan valid.